Gratitude and social support as predictors for fishermen's subjective well-being - Shaleh, Abdul Rahman; Rahayu, Anizar; Zubeir, Azlee; Istiqlal, Akhlis (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2020)
Everybody aspires and deserves some personal well-being. This kind of well-being is subjective, and it is shaped by the way individuals perceive and feel the situations surrounding their lives. This study aimed to investigate the effect of gratitude and social support on fishermen's subjective well-being. This study's subjects were 299 fishermen living in the coastal area of Pelabuhan Ratu, who were chosen through an accidental sampling technique. In collecting data, subjective well-being was measured using Flourishing Scale and Scale of Positive and Negative Experience, Gratitude Scale, which was based on Gratitude Resentment and Appreciation Test, and Social Support Scale that was based on Multidimensional Scale of Perceived Social Support. Multiple regression analysis showed that the entire independent variables significantly influenced subjective well-being. Meanwhile, each dimension's regressive coefficient on the independent variables showed four sub-variables that significantly influenced the dependent variables: sense of abundance, simple appreciation, appreciation to others, and family support.